Academic Information System Management To Improve Service Quality To Students During The Covid-19 Pandemicat Universities In Jambi Province - Dioputra, Sepryhatin; Wahidin, Didin; Iriantara, Yosal; Warta, Waska (CV. Inara, 2022)
Universities that have good academic service management quality standards are the goal in every university's efforts. In Jambi Province in particular, good management applied to a university is one of the important factors to improve the quality of service both for students, the community or for the university itself. Not a few universities whose academic service quality still does not meet the satisfaction threshold in the assessment, one of which is offline-based services that will usually hinder the delivery of existing information. UNAMA colleges (Universitas Stikom Dinamika Bangsa) and IAI Tebo in Jambi Province are universities where each delivery of academic information focuses on the use of computers and technology, both of these universities have implemented academic information system management, but each of these universities has advantages and disadvantages in the information system that is run, so a study is needed to be able to combine each of the advantages and disadvantages found in the two universities. By applying qualitative methods, it is hoped that it will provide useful research results,the focus of this research is directed at (1). Planning, (2). Implementation, (3). Evaluation (4). Solutions or follow-ups in improving the quality of academic services at universitiesusing Deming's cycle management theory. OnThis study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies.so from the results of this study can conclude a more complete management information system that can be applied to other universities, especially those that are still offline.